Hardcore, minority influence : a pivotal force to reverse the spiral of silence process dynamically. - Lang, Juan. (2008)
This study examines the minority influence of hardcore on the spiral of silence process. This study used two issues -- movie censorship (high involvement) and human cloning (low involvement). For each issue, a 2?2 factorial design (high vs. low consistency; high vs. low credibility) was employed to test the relationship between the independent variables (credibility and consistency) and dependent variables (opinion change and willingness to speak out).